Kekerasan Dalam Rumah Tangga dan Kesejahteraan Psikologis Istri dalam Perspektif Islam - Luh Putu Shanti Kusumaningsih (Psychopolytan : Jurnal Psikologi, 2024)
The case of domestic violence that has occurred recently in the community has become one of the topics that raise concern. When domestic violence occurs, it is usually women who are the most disadvantaged. Unfortunately, not many women dare to report cases of domestic violence they experience in the household and choose to remain silent without any resistance. The silence that most women choose over time will impact their psychological well-being as a wife. Islam has regulated the relationship between husband and wife in carrying out a household life that is sakinah, mawaddah and warrahmah where the husband must provide protection and treat his wife with love. The increasing number of domestic violence cases that occur shows that there are still many husbands who have not been able to carry out this mandate properly. This condition can lead to a decrease in psychological well-being (wellbeing) for the wife because she does not get protection from the priest in the family but instead harsh treatment resulting in feelings of fear and restlessness in living married life. This paper will discuss how domestic violence can affect the psychological well-being of wives in the household as well as provide a discourse on how to treat their wives from the perspective of Islamic Psychology.